Genital lesions in a female child: Approach to the diagnosis - Bhakthavatsalam Anitha; Ragunatha Shivanna (Wolters Kluwer Medknow Publications, 2018)
Genital lesions in a female child cause a lot of apprehension in the parents. Hence, thorough knowledge and proper approach to the diagnosis is very important. The aim of this article is to present an overview of the pattern of diseases affecting genitalia in a female child, significance of these diseases, and an approach to the diagnosis of these diseases. Most of these vulval dermatoses present with one of the four clinical scenarios such as pruritus with/without lesions, pain with/without lesions, discharge with/without lesions, and asymptomatic lesions. The approach to the diagnosis has been discussed accordingly. Diseases such as genital warts and genital herpes which are not common in this age group always raise the suspicion of child sexual abuse. There are certain adult vulval dermatoses such as chronic vulvovaginal candidiasis, which are not seen in prepubertal group.